Decrease in Circulating Dendritic Cell Precursors in Patients with Peripheral Artery Disease. (15th April 2015) - Kretzschmar, Daniel; Rohm, Ilonka; Schäller, Sebastian; Betge, Stefan; Pistulli, Rudin; Atiskova, Yevgeniya; Figulla, Hans-R.; Yilmaz, Atilla
Abstract : Peripheral artery disease (PAD) is a common manifestation of atherosclerosis. Inflammation is important for initiation and progression of the disease. Dendritic cells (DCs) as antigen-presenting cells play an important role in the immune system. Therefore, we hypothesize that, in patients with PAD, DCPs might be reduced in blood due to their recruitment into the vascular wall and induce a proinflammatory response. The numbers of myeloid DCPs, plasmacytoid DCPs, and total DCPs were analyzed by flow cytometry in blood of patients with PAD (n = 52 ) compared to controls (n = 60 ). Femoralis plaques (n = 12 ) of patients who underwent surgery were immunostained for CD209 and CD83 (mDCs) as well as CD304, CD123 (pDCs), and HLA-DR. In patients with PAD, a significant decrease in mDCPs, pDCPs, and tDCPs was observed. In immunostaining, markers indicative for mDCs (CD209: 16 versus 8 cells/0.1 mm 2, P = 0.02 ; CD83: 19 versus 5 cells/0.1 mm 2, P = 0.03 ) were significantly elevated in femoralis plaques compared to control vessels. We show for the first time that mDCPs, pDCPs, and tDCPs are significantly reduced in patients with PAD. Immunohistochemical analysis unraveled that the decrease in DCPs might be due to their recruitment into atherosclerotic plaques.